Synergistic combination of cytotoxic chemotherapy and cyclin‐dependent kinase 4/6 inhibitors in biliary tract cancers. Issue 1 (12th December 2021) - Arora, Mansi; Bogenberger, James M.; Abdelrahman, Amro M.; Yonkus, Jennifer; Alva‐Ruiz, Roberto; Leiting, Jennifer L.; Chen, Xianfeng; Serrano Uson Junior, Pedro Luiz; Dumbauld, Chelsae R.; Baker, Alexander T.; Gamb, Scott I.; Egan, Jan B.; et al.
Abstract: Background and aims: Biliary tract cancers (BTCs) are uncommon, but highly lethal, gastrointestinal malignancies. Gemcitabine/cisplatin is a standard‐of‐care systemic therapy, but has a modest impact on survival and harbors toxicities, including myelosuppression, nephropathy, neuropathy, and ototoxicity. Whereas BTCs are characterized by aberrations activating the cyclinD1/cyclin‐dependent kinase (CDK)4/6/CDK inhibitor 2a/retinoblastoma pathway, clinical use of CDK4/6 inhibitors as monotherapy is limited by lack of validated biomarkers, diffident preclinical efficacy, and development of acquired drug resistance. Emerging studies have explored therapeutic strategies to enhance the antitumor efficacy of CDK4/6 inhibitors by the combination with chemotherapy regimens, but their mechanism of action remains elusive. Approach and results: Here, we report in vitro and in vivo synergy in BTC models, showing enhanced efficacy, reduced toxicity, and better survival with a combination comprising gemcitabine/cisplatin and CDK4/6 inhibitors. Furthermore, we demonstrated that abemaciclib monotherapy had only modest efficacy attributable to autophagy‐induced resistance. Notably, triplet therapy was able to potentiate efficacy through elimination of the autophagic flux. Correspondingly, abemaciclib potentiated ribonucleotide reductase catalytic subunit M1 reduction, resulting in sensitization to gemcitabine. Conclusions: As such, these data provide robust preclinical mechanistic evidence of synergy between gemcitabine/cisplatin and CDK4/6 inhibitors and delineate a path forward for translation of these findings to preliminary clinical studies in advanced BTC patients.